LAND-USE CHANGE AND ITS ENVIRONMENTAL IMPACT IN THE HEIHE RIVER BASIN, ARID NORTHWESTERN CHINA - Qi Sh.; Luo F. (My University, 2006)
Rapid land-use change has taken place in many arid and semi-arid regions of China over the last decade as the result of demand for food for its growing population. The Heihe River Basin, a typical inland river basin of temperate arid zone in northwestern China, was investigated to assess land-use change dynamics by the combined use of satellite remote sensing and geographical information systems (GIS), and to explore the interaction between these changes and the environment. Images were classified into six land-use types: cropland, forestland, grassland, water, urban or built-up land, and barren land. The objectives were to assess and analyze landscape change of land use/cover in Heihe River Basin over 15 years from 1987 to 2002. The results show that (1) grassland and barren land increase greatly by 22.3, and 268.2 km2, respectively, but water area decreased rapidly by 247.2 km2 in the upper reaches of Heihe River Basin; (2) cropland and urban or built-up land increased greatly by 174.9, and 64.6 km2, respectively, but grassland decreased rapidly by 210.3 km2 in the middle reaches of Heihe River Basin; and (3) barren land increased largely by 397.4 km2, but grassland degraded seriously and water area decreased obviously by 313.3, and 21.7 km2, respectively in the lower reaches of Heihe River Basin. These results show that significant changes in land-use occur within the whole basin over the study period and cause severe environmental degradation, such as water environmental changes (including surface water runoff change, decline of groundwater table and degeneration of surface water and groundwater quality), land desertification and salinization, and vegetation degeneracy.
Keywords: LAND USE CHANGE; ENVIRONMENTAL CHANGE; HEIHE RIVER BASIN; ARID NORTHWESTERN CHINA